Pengaruh Pengaruh Model Project Based Learning berbantuan Media Canva Terhadap Keterampilan Menulis Teks Puisi pada Siswa SMP - Fitri, Nofia Rahmiatul; Tamsin, Andria Catri (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effect of the Project Based Learning (PjBL) model assisted by Canva media on poetry writing skills in eighth-grade students of SMP Negeri 3 X Koto Singkarak. The PjBL model was chosen because it encourages students to actively design real-life projects, stimulates creativity, collaboration, and in-depth idea processing. Canva media is used as an organizational tool and a medium for conveying material about poetry texts in an engaging manner. The research method used is quantitative with a quasi-experimental approach using a one-group pretest-posttest design. Data were collected through poetry writing tests before (pretest) and after (posttest) the application of the PjBL model assisted by Canva media. The research instrument was an assessment rubric that covered the suitability of the content to the theme/title, the use of diction and imagery, and the physical and spiritual structure of the poem. Data analysis included the Shapiro-Wilk normality test, Levene's homogeneity test, and a paired sample t-test to determine significant differences between the pretest and posttest. The results showed a significant improvement in students' poetry writing skills after implementing the Canva-assisted Project-Based Learning (PjBL) model. Students' average scores increased from 58.01 to 80.92. A paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. Therefore, it can be concluded that the Canva-assisted Project-Based Learning (PjBL) model is effective in improving students' poetry writing skills. This model not only provides knowledge and understanding of poetry but also facilitates the development of students' creativity, critical thinking, collaboration skills, and digital literacy. The use of Canva also provides visual and interactive support that facilitates students' understanding of poetry, making learning more engaging and meaningful.